Compatible models for Quercus spp. stand biomass and net primary production sensitive to precipitation and winter temperature in Eurasia - Andreevich Usoltsev, Vladimir; Omid Reza Shobairi, Seyed Omid Reza Shobairi; Stepanovich Tsepordey, Ivan (Macedonian Journal of Ecology and Environment, 2020)
Since ancient times, climate change has largely determined the fate of human civilization, which was related mainly with changes in the structure and habitats of forest cover. In the context of current climate change, one must know a change of forest sustainability and productivity under future climate conditions. For this purpose, the authors compiled the database of biomass and net primary production (NPP) of Quercus spp. on Eurasian area in the amount of 663 and 260 sample plots correspondingly and used the methodology of multivariate regression analysis. The first attempt of modeling changes in compatible component composition of biomass and NPP on the Trans-Eurasian hydrothermal gradients involving regional peculiarities of age and morphology of the forests is fulfilled. It is found significant positive relationship of aboveground and total biomass with the mean temperature of January, and negative relationship with the level of moisture, was established. For the biomass of foliage, branches and roots, the positive pattern is only for wet regions, but as we move towards arid regions, this relationship becomes negative, and in 3D interpretation, the pattern looks as a propeller -like surface. The patterns of changes in the total and aboveground NPP are similar to the corresponding patterns for total and aboveground biomass, and the patterns of changes in the NPP of foliage, branches, roots and stems in climatic gradients correspond to the same propeller-like 3D picture. It is necessary to create compatible transcontinental models of biomass and NPP, sensitive to climate change, for each tree species (genus) separately and to find out the biological and ecological reasons for the differences in the results.